2016
DOI: 10.1016/j.polymer.2015.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate) nanotubes in AAO templates: Designing nanotube thickness and characterizing the T-confinement effect by DSC

Abstract: We used differential scanning calorimetry (DSC) to study the effect of confinement on the glass transition temperature (T g) of poly(methyl methacrylate) (PMMA) nanotubes supported in anodic aluminum oxide (AAO) templates. We created nanotubes by wetting templates with polymer melts and developed a design equation relating tube thickness (t tube) with bulk radius of gyration (R g): (t tube ≈ 2 R g + 9 nm). The results indicate that t tube depends on overall conformation and size of the polymer coils and can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 143 publications
1
19
0
Order By: Relevance
“…Besides crystallization kinetics, other features related to polymer structure, such as crystal orientation and phase transitions inside the AAO template nanopores, have also been the focus of recent research ,,, as recently reviewed by Muller et al Moreover, it has been also reported that the glass transition temperature of poly­(methyl methacrylate) (PMMA) infiltrated in AAO nanocavities differs from that of bulk and the value increases as the diameter of pore nanocavities decreases . Related to PMMA, in the study of the glass transition temperature of the polymer by thermal annealing experiments, Xue and co-workers observed a double glass transition temperature of the PMMA inside the AAO template.…”
Section: Introductionmentioning
confidence: 99%
“…Besides crystallization kinetics, other features related to polymer structure, such as crystal orientation and phase transitions inside the AAO template nanopores, have also been the focus of recent research ,,, as recently reviewed by Muller et al Moreover, it has been also reported that the glass transition temperature of poly­(methyl methacrylate) (PMMA) infiltrated in AAO nanocavities differs from that of bulk and the value increases as the diameter of pore nanocavities decreases . Related to PMMA, in the study of the glass transition temperature of the polymer by thermal annealing experiments, Xue and co-workers observed a double glass transition temperature of the PMMA inside the AAO template.…”
Section: Introductionmentioning
confidence: 99%
“…Ellipsometry, capillary dilatometry, and X‐ray reflectivity require relatively flat, continuous films to accurately measure T g . While DSC has been used to study 2D‐confined (where two dimensions are restricted to the nanoscale) polymer systems through anodized aluminum oxide (AAO) template‐supported nanorods and nanotubes, sample geometry and interfacial interactions were somewhat limited by template constraints. Additionally, these techniques do not enable location‐specific measurements in the presence of a free surface without costly and time‐intensive scattering and reflectivity studies.…”
Section: Fluorescence To Measure Tg and Physical Aging In Single‐compmentioning
confidence: 99%
“…Furthermore, similar polymer phase separations and transformation behaviors at the microscale have also been observed [34,35,36,37,38]. Because of the success of the AAO templating method, many publications have explored various AAO applications such as thermal and physical properties of polymer nanostructures under nanoconfinement conditions, fabrication of higher−order nanostructures, polymerization and crystallization in AAO templates, and the double infiltration nanoencapsulation process [39,40,41,42,43,44,45,46,47,48,49].…”
Section: Introductionmentioning
confidence: 96%